Promoting trustworthy file sharing: A community-governed dApp approach - Chong-Gee Koa; Swee-Huay Heng; Ji-Jian Chin (PLoS ONE, 2025)
In the cyber digital world, file sharing has become a cornerstone of global connectivity, facilitating the exchange of media, information, and resources among people worldwide. File sharing is already a norm in our daily lives, with many existing platforms allowing users to download shared content without verification or with only basic verification. Hence, the trustworthiness of the shared content is a concern. Meanwhile, blockchain technology has evolved over the last 15 years since its introduction, renowned for its decentralised, secure, and transparent system enabling efficient transactions, traceability across various industries. To address the mentioned open issue, we introduce a decentralised application (dApp) called Filetherst which is backed by ETHERST, a blockchain-based PKI. Filetherst focuses on ensuring shared files are trustworthy through the involvement of the virtual community in evaluating trustworthiness through actions triggered by community members. The foundational principle lies in encouraging users to actively take part in governing the platform, fostering a culture of transparency and accountability, preventing users from using multiple fake accounts to create false trustworthiness. Filetherst is the first dApp that leverages the Ethereum ERC-20 token to establish a self-governing network aimed at addressing the dissemination of harmful and inappropriate content within a virtual community.